2022
DOI: 10.35762/aer.2021.44.1.10
|View full text |Cite
|
Sign up to set email alerts
|

Risk Assessment of Total Mercury (T-Hg) in Commercial Seafood Marketed in Bangkok, Thailand

Abstract: Seafood is recognized as the high protein source of human consumption. However, it is hampered by mercury contamination. The objectives of this study are to determine total mercury (T-Hg) levels in edible portions of commercial seafood available in Bangkok’s supermarkets, and to evaluate the potential risks from mercury through seafood consumption. Total 32 species, including 22 fish, 4 cephalopod and 6 shellfish, were purchased from super-markets. Fish samples were dissected in 3 parts comprised of flesh, gil… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 30 publications
0
1
0
Order By: Relevance
“…This result agrees with the study of Arbsuwan [42], which found that Indo-Pacific mackerel from the pier in the Khlong-yai district was safe from cadmium's adverse effects on human health. Ritonga et al [43] also found that Indian mackerel, belonging to the same family as Indo-Pacific mackerel from the market in Bangkok, was safe from mercury's adverse effects on human health.…”
Section: Risk Assessment Of Toxic Elements Through Fish Consumptionmentioning
confidence: 98%
“…This result agrees with the study of Arbsuwan [42], which found that Indo-Pacific mackerel from the pier in the Khlong-yai district was safe from cadmium's adverse effects on human health. Ritonga et al [43] also found that Indian mackerel, belonging to the same family as Indo-Pacific mackerel from the market in Bangkok, was safe from mercury's adverse effects on human health.…”
Section: Risk Assessment Of Toxic Elements Through Fish Consumptionmentioning
confidence: 98%